Evaluating the SPBE-Based Monitoring and Evaluation System for Village Facilitators’ Performance - Resmita, Tenti; Sartika, Ika (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Digital transformation in public governance has driven the implementation of the Electronic-Based Government System (EBGS) as a key framework for enhancing efficiency, accountability, and transparency in public service delivery, including in village development management. This study aims to evaluate the effectiveness of the EBGS-based monitoring and evaluation system in assessing the performance of Professional Village Facilitators (PVFs) within the context of village assistance programs. A descriptive qualitative approach was employed, drawing primarily on document analysis, including the 2024 PVF Performance Evaluation SOP, EBGS evaluation reports, and academic references. Findings indicate that the evaluation system, based on the DRP and DRP Evkin applications, has successfully integrated daily activity reporting and qualitative supervisor assessments into a streamlined digital platform. The system applies a balanced scoring mechanism that combines quantitative metrics (working hours) and qualitative assessments (work competencies). The adoption of EBGS has enabled real-time performance tracking and reduced data distortion at the field level. Nonetheless, challenges persist, such as delays in supervisor assessments, vacant evaluator positions, and limited infrastructure capacity in certain regions. The system has also incorporated risk management principles by classifying technical and structural risks and adopting mitigation strategies grounded in both technological and organizational structures. These findings suggest that EBGS holds significant potential for improving performance evaluation governance at the village level. However, institutional reinforcement and technical support remain crucial. Policy recommendations include enhancing the digital capacity of PVFs, expanding system features, and strengthening infrastructure in remote areas to ensure equitable and sustainable EBGS implementation.